Peran Administrasi Publik dalam Pembangunan Berkelanjutan di Era Digital - Suherman; Hartutik, Dwi; Lastri, Novelma (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Sustainable development has been at the top of the agenda in global policies, including in Indonesia, to achieve a balance between economic growth, social welfare, and environmental sustainability. Along with the development of the digital era, public administration has a strategic role in accelerating the implementation of sustainable development policies through the use of digital technology. Digital transformation in public administration allows for increased efficiency, transparency, and community involvement in policy decision-making. However, the main challenges in its implementation include limited infrastructure, digital divides, and the readiness of human resources to face technological changes. This research aims to analyze how public administration can contribute to accelerating sustainable development in the digital era. Using a literature study method, this study examines various academic sources, including scientific journals, books, and policy reports from international institutions such as the United Nations Development Programme (UNDP) and the World Bank. The results of the study show that the digitization of public administration increases transparency and accountability in governance. In addition, the use of technologies such as e-Government, Artificial Intelligence (AI), and Big Data Analytics has been proven to accelerate the implementation of sustainable development policies. However, there are still challenges in terms of regulation, data security, and public readiness to access digital services. With the right strategy, public administration can play a key role in accelerating sustainable development in the digital era.